Penerapan Kurikulum Merdeka pada Pembelajaran PAI di Madrasah: Studi Evaluatif Menggunakan Model CIPP - Ahmad Abrani Noor; Nuril Huda (MAN 4 Kota Pekanbaru, 2026)
The implementation of the Merdeka Curriculum in Islamic Religious Education (IRE) at madrasahs has become an important effort to improve the quality of learning and respond to current educational challenges. This study aims to analyze the implementation of the Merdeka Curriculum in IRE learning using the Context, Input, Process, and Product (CIPP) evaluation model. The research employed a qualitative approach through a literature review by examining various academic journals, books, and government policy documents related to curriculum implementation and educational evaluation. The findings indicate that the Merdeka Curriculum encourages more flexible, contextual, and student-centered learning practices in madrasahs. In addition, the curriculum contributes to strengthening students’ character development, critical thinking, and social competence. However, several challenges are still found, particularly regarding teachers’ readiness, instructional adaptation, and the availability of educational facilities. Therefore, the CIPP model can be used as a comprehensive evaluation framework to support the improvement of PAI learning implementation in madrasahs.